Modeling of Glass Parts of Kinescopes Acceptance Inspection - Vaišvila, A; Kalnius, R.; Eidukas, D. (Elektronika ir Elektrotechnika, 2004)
There are given mathematical models for calculation of kinescopes glass parts - conuses and screens acceptance inspection probabilistic characteristics, when level of defectiveness of product is described by probabilistic beta-distribution. Received models estimates influence of such main factors as: mistakes of products classification, ration of regenerable and recoverable products flows values, parameters of inspection plans, average level of defectiveness of production flow, degree of maladjustment of technological process and volumes of multiply recursive flows. Ill. 5, bibl. 9 (in Lithuanian; summaries in Lithuanian, English, Russian).